1984
DOI: 10.2307/3576360
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-Induced Mutagenicity and Lethality in Ames Tester Strains of Salmonella

Abstract: Mutation and killing induced by X radiation and 60CO gamma radiation were studied in six different histidine-requiring auxotrophs of Salmonella typhimurium. Strain TA100, which is sensitive to base-pair substitutions, and strains TA2637 and TA98, which are sensitive to frameshifts, carry the pKM101 plasmid and exhibit significantly higher radiation-induced mutations compared to their plasmidless parent strains TA1535, TA1537, and TA1538, respectively. Among the plasmid-containing strains, TA98 and TA2637 are m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 42 publications
0
6
0
1
Order By: Relevance
“…Incubation in the presence of a mutagen causes a back mutation, restoring the wild type histidine operon, and results in histidine-independent colony growth which is then scored (Maron & Ames, 1983). In addition to testing chemical substances, the Ames test has also been used for screening the mutagenicity of ionizing radiation (Imray & MacPhee, 1981;Isildar & Bakale, 1984), ultra violet radiation (MacPhee & Schoeffel, 1981), and extralow-frequency radiation associated with electromagnetic fields (Moga & Obringer, 1996).…”
Section: Determination Of Mutagenicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Incubation in the presence of a mutagen causes a back mutation, restoring the wild type histidine operon, and results in histidine-independent colony growth which is then scored (Maron & Ames, 1983). In addition to testing chemical substances, the Ames test has also been used for screening the mutagenicity of ionizing radiation (Imray & MacPhee, 1981;Isildar & Bakale, 1984), ultra violet radiation (MacPhee & Schoeffel, 1981), and extralow-frequency radiation associated with electromagnetic fields (Moga & Obringer, 1996).…”
Section: Determination Of Mutagenicitymentioning
confidence: 99%
“…TA98 possesses a hisD3052 mutation in the hisD gene coding for histidinol hydrogenase with eight repetitive GC residues near the site of a -1 frameshift mutation (Isono & Yourna, 1974), while TA100 contains a mutation in the hisG46 gene coding for the first enzyme of histidine biosynthesis, in which an A-T in the wild type sequence has been substituted with a G-C, changing a proline to leucine (Barnes et al, 1982). These strains have been used previously for radiation-induced mutagenicity studies and have been found appropriate and sensitive to the mutagenic action of radiations (Imray & MacPhee, 1981;Isildar & Bakale, 1984. Detailed methods for conducting the Ames test have been published else-where (Maron & Ames, 1983;Mortelmans & Zeiger, 2000).…”
Section: Determination Of Mutagenicitymentioning
confidence: 99%
“…Toutefois, les résultats se sont avérés peu reproductibles entre différents laboratoires et, dans les conditions standard d'utilisation, la sensibilité est faible puisque les doses donnant une réponse mesurable sont de l'ordre de quelques dizaines à quelques centaines de grays [1,15,20]. Des modifications des souches [22] ou du protocole [35] ont permis d'obtenir des sensibilités de l'ordre de quelques grays.…”
Section: Les Rayonnements Ionisantsunclassified
“…Since the early 1980s, there have been several trials to monitor the effects of ionizing radiation on microorganisms using bacterial cells including the Ames test [1,2]. Before finally applying these methods, several limitations including detection time, detection methods, and sensitivity must be overcome.…”
Section: Introductionmentioning
confidence: 99%